Hyperhomocysteinaemia: a risk factor for extracranial carotid artery atherosclerosis. - Clarke, R; Fitzgerald, D; O'Brien, C; O'Farrell, C; Roche, G; Parker, R; Graham, I (1992)
Hyperhomocysteinemia arising from impaired methionine metabolism, and usually due to a deficiency of cystathionine beta-synthase is a significant and independent risk factor for symptomatic vascular disease. It is not known if hyperhomocysteinemia in apparently healthy asymptomatic subjects is associated with atherosclerosis and whether such a relationship is independent of conventional risk factors. The prevalence of asymptomatic extracranial carotid artery atherosclerosis was determined by duplex ultrasound examination in 25 obligate heterozygotes with respect for cystathionine beta-synthase deficiency (whose children were known to be homozygous for this genetic defect) and in 21 controls. Hyperhomocysteinemia was determined by a standard methionine-loading test and conventional risk factors were also recorded. Twelve of 25 obligate heterozygotes and 8 of 21 normal controls had evidence of extracranial carotid artery atherosclerosis. Hyperhomocysteinemia as a genetic trait was not a significant risk marker, but the actual homocysteine level was associated with an increased risk of carotid disease. After adjustment for the effects of other significant risk factors, the odds ratio of hyperhomocysteinemia for carotid disease was 1.038 per unit increase in homocysteine level (P = 0.03). Hyperhomocysteinemia is a weak risk factor for asymptomatic extracranial carotid atherosclerosis and the relative risk associated with this genetic trait is less than that observed in a study of patients presenting with clinical manifestations of vascular disease.